Cher Antoine ou l’amour raté de Jean Anouilh – de l’absence à la présence de personnage - Kucharuk, Sylwia (Quêtes littéraires, 2012)
The eponymous hero of this little-known play by Jean Anouilh is perceived by other protagonists as absent. Nevertheless, his presence is becoming more and more vivid with the development of the plot, which is illustrated by the analysis presented in the article. It shows the process in which the absent hero transforms into a character fully present in the text. The detailed analysis of the character’s presence in particular space-time dimensions, as well as the actant analysis prove that the main character pretends to be absent from the beginning of the play in order to achieve a definite goal.